Dental Assisting In Specialized Fields: Pediatric, Orthodontic, And Periodontic Practices (Journal of Namibian Studies : History Politics Culture, 2022)
This abstract explores the role of dental assistants in specialized fields, focusing on pediatric dentistry, orthodontics, and periodontics. Dental assistants in these areas perform unique duties tailored to the needs of young patients, orthodontic patients undergoing alignment treatment, and individuals receiving periodontal care.